Clinico-etiologic correlates of onychomycosis in Sikkim - Adhikari Luna; Gupta Atrayee; Pal Ranabir; Singh T.S.K (Wolters Kluwer Medknow Publications, 2009)
Aims and objectives: The etiological spectrum of any superficial mycosis is largely dependent on the flora in the immediate environment of the individual. It is influenced by the geographic, climatic and occupational factors. The study is basically to formulate baseline data for the species prevalence of various dermatophytes in patients with onychomycosis attending the Central Referral Hospital, Gangtok, Sikkim. Materials and Methods: Thirty-four clinically suspected cases of onychomycosis were subjected to mycological studies. Results: Thirty-two (94.12%) cases were positive for fungal elements by direct microscopy and 28 (82.35%) by culture. Young adults in the age group of 21-30 years were mainly affected. The male:female ratio was 1.125:1. Dermatophytes were isolated in 18 cases (64.29%). Trichophyton tonsurans (44.44%) was the most common isolate followed by T. mentagrophytes (22.22%), T. rubrum (11.11%), T. verrucosum (11.11%) and Microsporum audouinii (11.11%). Apart from dermatophytes, Aspergillus niger (21.43%) and Penicillium marneffei (14.28%) were also isolated. Conclusion: Dermatophytes, mainly T. tonsurans, as well as moulds other than dermatophytes were isolated from onychomycosis patients in Gangtok, Sikkim.